Prácticas de enseñanza de Lógica-Matemática en Inicial II en el Centro Municipal en Educación Inicial Empleados Municipales. - Maldonado Rivera, Evelin Cristina (2016)
In this research is to analyze how teaching practices give mathematical logic in early February in the Municipal Center for Early Education Municipal Employees with children aged four to five years old. The planning, methodologies, teacher-student interaction, assessment tasks and categories investigated. The document is divided into: description of the problem with history, importance and scope and boundaries, also presentation of problems with their respective objectives, besides a theoretical framework in which themes relating develop the pedagogical practice in the initial level, mathematics teaching, resources and materials for the acquisition of mathematical logic. In addition, tools and techniques applied in research and observation records, diaries and applied fields presents interviews. The analysis of the results, based relationships established between the teaching practices at the initial level and mathematical logic as an essential part of the educational process. The teaching, knowledge and children are key elements in the development of planning and interactions that occur. The teaching-learning process logic mathematic developed Center allows participation, troubleshooting analyzes information, explore your surroundings and use thought for social interaction, through the use of experience, handling and wetted. In the Children's Center it is working with methodological processes according to evolutionary development.